Economic, social and environmental impacts attained by the use of the effluents generated within a small-scale biorefinery concept - Lopes, Tiago (2020)
ABSTRACT: Biorefineries are emerging as the proper route to defeat climate change and other social, socio-economic and environmental concerns. So far, no residual lignocellulosic biomass-based biorefineries have been yet industrially implemented, mainly due to its economic viability. This article exposes some elements that may help overcome the bottlenecks associated to its social, economic and environmental sustainability: small-scale approaches, biomass valorisation through added-value products and near-zero effluent.